Соціальні бальні танці у сучасному культурному просторі: психосоціальний аспект - Кашевський, Олександр Васильович; Kashevskyi, O. V. (Рівненський державний гуманітарний університет, наукове товариство "Афіна", 2015)
Подається загальна характеристика соціальних танців як соціокультурного явища. Висвітлюються психосоціальні можливості впливу танцювальної культури на особистість на прикладі анкетування учасників студентського клубу сучасного бального танцю «СК-ДЕНС» Східноєвропейського національного університету ім. Лесі Українки. This paper shows general characteristic of social (partner) dances as a social and cultural phenomenon. With a view to express main psychosocial principles of social (partner) ballroom dances, next objectives are stated in this survey: to indicate general characteristic of social (partner) ballroom dance as a social and culture phenomenon; to illustrate psychosocial abilities of dancing culture to influence a personality through polling members of Student’s Contemporary Ballroom Dance Club «SK-Dance» of Lesia Ukrainka East-European National University. Social (partner) dance is a phenomenon whose name shows an alternative to competitive dance. It is based upon the constant desire of a person to move, doing this with a masterly skill and in style. And above all, this motion becomes a communication mode in the social medium, when an amateur dancer expresses his or her emotions through choreographic improvisation. With the purpose of studying psychosocial functions of this kind of dance, the author has done experimental works that involved polling members of Student’s Contemporary Ballroom Dance Club «SK-DANCE» of Lesia Ukrainka East-European National University. The main results of this study give us an option of making a conclusion about the influence of being engaged in social (partner) dancing in their psychoemotional state and social culture of the club’s members. The classes at the club of social (partner) dances have a high level of psychosocial functions, and this is one of the means of young person’s self-expression.
Social (Partner) Ballroom Dances in Contemporary Cultural Context: Psychosocial Aspect
Keywords: соціальний танець; сучасний бальний танець; студентський клуб; психосоціальний аспект; social (partner) dance; contemporary ballroom dance; student’s club; psychosocial aspect